KAJIAN PERSEPSI KONSUMEN TERHADAP PENGGUNAAN OBAT HERBAL(KASUS DI UNISMA BEKASI) - Rani, Ismarani (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2013)
This study aimedto investigate the characteristicsof consumersinUnismaBekasiherbalmedicine, herbaldrugsthat consumers demand, and the factors thataffect consumersin theuse ofherbalmedicine. The method usedby thedescriptivemethodof datacollection techniquesthrough thedistribution of questionnaires, and field observations. Samplingwithnon-probabilitysamplingmethodispurposiveorjudgment sampling.The results showedthat thefaculty and staffUnismaBekasihavea positive perception ofthe use ofherbalmedicines. Respondentsuse atype ofherbalmedicineasalternativemedicine(69,4%), herbalmedicinecapsule-shapedtypeis preferred(68,1%), and thefactorsthat influencerespondents'useof herbalmedicineisa friendinformation(73,6%).